ITPKC polymorphism (rs7251246 T > C), coronary artery aneurysms, and thrombosis in patients with Kawasaki disease in a Southern Han Chinese population - Liu, Jie; Yuan, Piaoliu; Pang, Yusheng; Su, Danyan (Frontiers in Immunology, 2023)
Objectives: Kawasaki disease (KD) is a commonly acquired pediatric systemic vasculitis disease resulting in coronary artery aneurysm (CAA). The relationship between the ITPKC polymorphism (rs7251246) and the severity and susceptibility to KD in the Han Chinese population in Southern China remain unclear. Methods: We enrolled 262 children as controls and 221 children with KD (46 [20.8%] with intravenous immunoglobulin resistance and 82 [37.1%] with CAA). The relationship between the ITPKC rs7251246 polymorphism, KD susceptibility, and CAA formation was investigated. Results: While the ITPKC rs7251246 T>C polymorphism was not significantly associated with KD susceptibility, it was significantly associated with the CAA risk in children with KD [CC/CT vs. TT: adjusted odds ratio [OR] 2.089, 95% confidence interval [CI] 1.085–4.020]. Male children with the rs7251246 CC genotype had a significantly higher risk of thrombosis [CC vs. CT/TT: adjusted OR 3.987, 95% CI 1.084–14.666]. Children with KD, especially those with CAA, had a significant downregulation of ITPKC mRNA compared to healthy children. ITPKC mRNA levels were lower in children with CAA who developed thrombosis (P=0.039). In children with KD, the CC genotype showed lower mRNA levels of ITPKC (P=0.035). Conclusions: The ITPKC rs7251246 T>C polymorphism may be a risk factor for CAA and thrombosis in children with KD in the Han Chinese population, likely due to differences in mature mRNA levels caused by interference of RNA splicing. Dual antiplatelet therapy for thrombosis is recommended for male children with the rs7251246 CC genotype.